The Use of Make-a-Match Model in Improving Vocabulary Listening Skills in Arabic Language Learning for Elementary Students - Usnaini, Usnaini; Nuha, Muhammad Afthon Ulin (Kalimatuna: Journal of Arabic Research, 2024)
This study investigates the effectiveness of the Make-a-Match model in improving vocabulary listening skills in Arabic language learning for elementary school students. The research method used is library research with a literature review approach. This literature review collects and analyses relevant articles, books, journals, and other reference sources using the Make-a-Match model in Arabic language learning. The analysis results show that the Make-a-Match model can effectively improve vocabulary listening skills in Arabic language learning for elementary school students. This model encourages active student engagement in learning, increases learning motivation, and helps students strengthen associations between vocabulary and meaning. Overall, this study provides a better understanding of the use of the Make-a-Match model in improving vocabulary listening skills in Arabic language learning for elementary school students.